The Failure of the Global Plastics Treaty Conference and Its Implications for Developing Countries - Mar'atus Solikhah (Worldwide Research Publishing, 2025)
Plastic pollution has become one of the most serious environmental challenges of the 21st century, with more than 11 million tons of plastic entering the oceans each year. Efforts to form the Global Plastic Treaty are expected to be a multilateral instrument that is able to systematically reduce plastic pollution. However, the conference, which took place in 2024–2025, failed to reach a consensus due to the tug-of-war between developed countries, developing countries, the plastics industry, and civil society organizations. This study aims to analyze the factors that cause the failure of the global plastics treaty conference, assess its implications for developing countries, and provide recommendations for alternative policy strategies for the Global South countries. The research uses a qualitative approach with a descriptive-analytical method. Data were collected through documentation studies of official conference documents, reports of international organizations, academic articles, as well as semi-structured interviews with sources from academics, diplomats, and environmental activists. The analysis was carried out using thematic analysis techniques and source triangulation. The results show that the failure of the global plastics agreement is triggered by differences in fundamental interests, the dominance of the industry lobby, and the weak consensus mechanism. By implication, developing countries bear greater environmental and socio-economic burdens, such as increasing marine pollution, vulnerability to informal workers recycling, and limited access to environmentally friendly technologies. The recommendations offered include the formation of a South-South diplomacy coalition, strengthening domestic capacity, and innovative financing mechanisms such as green bonds or plastic taxes.